Manajemen Pendidikan Karakter Religius Berbasis PAI: Temuan Kualitatif dari FGD Stakeholder Sekolah Dasar Islam - Suriansyah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study investigates the management of religious character education based on Islamic Religious Education through qualitative evidence derived from stakeholder focus group discussions in an Islamic elementary school. Using an interpretive case study design, the research analyzes how strategic planning, program implementation, and evaluation are constructed and negotiated within the organizational processes of the school. The findings reveal that strategic planning is largely centralized and policy driven, limiting empirical needs analysis and meaningful stakeholder participation. Program implementation depends strongly on individual teacher commitment, while institutional coordination mechanisms remain underdeveloped, producing fragmented pedagogical practices across classrooms. Evaluation and control are dominated by administrative compliance indicators, with limited attention to measuring the internalization of religious values and to establishing a continuous improvement cycle. These patterns indicate that religious character education is sustained more by symbolic conformity than by organizational learning. The study contributes theoretically by positioning stakeholder interaction as the central analytical unit in character education management and contributes methodologically by demonstrating the value of cross-stakeholder focus group discussions in capturing deliberative processes within school governance.